2018
DOI: 10.1242/jcs.215178
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cAMP exerts positive feedback on mitochondrial Ca2+ uptake via the recruitment of Epac1

Abstract: We have previously demonstrated in H295R adrenocortical cells that the Ca-dependent production of mitochondrial cAMP (mt-cAMP) by the matrix soluble adenylyl cyclase (sAC; encoded by ) is associated with enhanced aldosterone production. Here, we examined whether mitochondrial sAC and mt-cAMP fine tune mitochondrial Ca metabolism to support steroidogenesis. Reduction of mt-cAMP formation resulted in decelerated mitochondrial Ca accumulation in intact cells during K-induced Ca signalling and also in permeabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 62 publications
3
15
0
Order By: Relevance
“…This may suggest that our FRET system does not have sufficient spatial resolution to detect discrete microdomains of cAMP (44), that the size of the cAMP increase is below the limit of detection, or that cAMP increases in mitochondria and not in the cytosol. This last hypothesis would be supported by a recent paper that showed that aldosterone increases selectively the activity of the soluble adenylyl cyclase in the mitochondria and that the inhibition of EPAC reduced mitochondrial Ca 2ϩ uptake, in a similar fashion to what was observed in the present contribution (45). It would be unlikely that EPAC, instead, is activated in a cAMP-independent fashion as this has never been reported previously.…”
Section: Htas2r46 Regulates Mitochondrial Calcium Bufferingsupporting
confidence: 88%
“…This may suggest that our FRET system does not have sufficient spatial resolution to detect discrete microdomains of cAMP (44), that the size of the cAMP increase is below the limit of detection, or that cAMP increases in mitochondria and not in the cytosol. This last hypothesis would be supported by a recent paper that showed that aldosterone increases selectively the activity of the soluble adenylyl cyclase in the mitochondria and that the inhibition of EPAC reduced mitochondrial Ca 2ϩ uptake, in a similar fashion to what was observed in the present contribution (45). It would be unlikely that EPAC, instead, is activated in a cAMP-independent fashion as this has never been reported previously.…”
Section: Htas2r46 Regulates Mitochondrial Calcium Bufferingsupporting
confidence: 88%
“…EPAC1 in mitochondria has gained increased attention recently and has been suggested to play a role in regulating MCU activity in H295R adrenocortical cells and HeLa cells as well as MCU activity and OXPHOS activity in isolated cardiac mitochondria from mouse (Szanda, Wisniewski, Rajki, & Spät, ; Wang et al, ). EPAC1 has not yet been demonstrated in brain mitochondria (to our knowledge), but here we provide pharmacological evidence for its functional presence.…”
Section: Discussionmentioning
confidence: 99%
“…and OXPHOS activity in isolated cardiac mitochondria from mouse (Szanda, Wisniewski, Rajki, & Spät, 2018;Wang et al, 2016). EPAC1…”
Section: H295r Adrenocortical Cells and Hela Cells As Well As Mcu Actmentioning
confidence: 99%
“…Importantly, cAMP has recently emerged as a potent regulator of mitochondrial metabolism. The mitochondrial matrix holds a unique cellular cAMP nanodomain independent of the cytosol [ 16 , 17 ], and its targeting has been even implicated in the preservation of cardiomyocyte function [ 18 ]. Mitochondrial cAMP nanodomains seem to embrace a unique subset of members of the adenylyl cyclase (AC) family — the soluble AC (sAC) [ 16 , 19 ] — and the phosphodiesterase (PDE) family — the dual-specific PDE2, the latter has been linked to both cardiac and lung injury models [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial matrix holds a unique cellular cAMP nanodomain independent of the cytosol [ 16 , 17 ], and its targeting has been even implicated in the preservation of cardiomyocyte function [ 18 ]. Mitochondrial cAMP nanodomains seem to embrace a unique subset of members of the adenylyl cyclase (AC) family — the soluble AC (sAC) [ 16 , 19 ] — and the phosphodiesterase (PDE) family — the dual-specific PDE2, the latter has been linked to both cardiac and lung injury models [ 20 , 21 ]. Next to sAC and PDE2, the exchange protein directly activated by cAMP (Epac)1 [ 19 , 22 ], and the A-kinase anchoring family member AKAP1 also maintain mitochondrial function [ 23 ] ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%